Comparative Study of Date Syrup Decolourization Efficiency with Ion Exchange Resins and Bone Char - ROFEHGARI-NEJAD*‡, LEILA; PIROOZIFARD, MIRKHALIL; ASEFI, NARMELA; TABIBI-AZAR†, MAHNAZ; ASHRAFI‡, ROGIEH (Asian Journal of Chemistry, 2024)
Date syrup is an important date by-products with about 67-72 % solids containing ca. 95 % reducing sugars. This product can be used as sweetener in different food industries but its brownish colour is a limiting factor. The aim of this work is to investigate the possibility of date syrup's colour substances removal by bone char and ion exchange resins. In this study decolourization effect of bone char and Amberlit IRA 410 (a strongly anionic resin) was studied in the form of factorial experiment using completely randomized design, contact time considered to be 10, 20, 30 and 60 min and the decolourizing substances quantities were 2, 4, 6, 8, 10, 20 and 30 %. Satisfactory result was obtained and decolourization rate for bone char and ion exchange resin was 89 and 87.6 %, respectively. Some chemical characteristics of decolourized date syrup was also investigated. The results indicated that replacement of invert sugar and glucose syrup with date liquid sugar would be possible.